Embracing Complexity: Ecological Designs for Living Landscapes - Marta Brocki; Nina-Marie Lister (Oz, 2014)
We are in the age of New Ecology. A paradigm shift in ecological thinking has unfolded over the last 25 years, and with it, a slow recognition of the inherent and fundamental complexity that shapes and defines our living world.